The Effect of media types on the growth of insect pathogenic fungi (Aschersonia placenta) - Sudiarta, I Putu; Hartha , I Komang Gede Suweca; Yuliadhi , Ketut Ayu; Wirya, Gusti Ngurah Alit Susanta; Selangga, Dewa Gede Wiryangga; Suputra , I Putu Wirya; Listihani, Listihani (Universitas Lampung, 2025)
Bali has favorable conditions for the production and expansion of citrus plantations. However, citrus cultivation in Bali often faces challenges, including reduced yield caused by pest infestations and pathogenic diseases. One significant pest affecting citrus plants is the whitefly. A potential method for controlling whiteflies is the use of natural enemies. The entomopathogenic fungus Aschersonia placenta is one of natural enemy that can effectively manage whitefly infestations. However, the succesful utilization of A. placenta requires a specialized approach, particularly in selecting an appropriate growth medium. This study aimed to investigate the impact of different growth media on the development of the entomopathogenic fungus A. placenta. The research began with field sampling, followed by the isolation and morphological identification of A. placenta to obtain a pure culture. Subsequently, media tests were conducted to evaluate fungal growth. Nine treatments were implemented to examine the impact of different media: (1) Water Agar (WA), (2) Potato Dextrose Agar (PDA), (3) Potato Sucrose Agar (PSA), (4) Water Agar + Weaver Ant Eggs Flour (WA-WAEF), (5) Potato Dextrose Agar + Weaver Ant Eggs Flour (PDA -WAEF), (6) Potato Sucrose Agar + Weaver Ant Eggs Flour (PSA-WAEF), (7) Water Agar + Cricket Flour (WA-CF), (8) Potato Dextrose Agar + Cricket Flour (PDA-CF), and (9) Potato Sucrose Agar + Cricket Flour (PSA-CF). The results demonstrated that incorporating cricket insect flour (Gryllidae: Orthoptera) or weaver ant egg flour (Oecophylla smaragdina) into potato sucrose media provided the most optimal growth environment for A. placenta.